Reduced sea water pH disrupts resource assessment and decision making in the hermit crab Pagurus bernhardus - de la Haye, K.L.; Spicer, J.I.; Widdicombe, S.; Briffa, M. (Animal behaviour, 2011)
The decisions that animals make are based on information gathered from their environment, and can have consequences for their fitness and survival. Such processes can be disrupted by environmental change. Hermit crabs find and select the gastropod shells they inhabit using chemical and visual cues, and tactile assessment. The choice of an optimal shell is important since it provides shelter against environmental extremes and protection against predators; inhabiting a suboptimal shell can also reduce fecundity. Hermit crabs are subject to cyclical reductions in the pH of the water in the intertidal rock pools that they inhabit, and such reductions may be further exacerbated by climate change. Reduced sea water pH, a consequence of ocean acidification and leaks from geological storage sites, has already been shown to disrupt the behaviour of marine animals. We investigated the effects of reduced sea water pH on the shell assessment and selection behaviour of the hermit crab Pagurus bernhardus. Under highly reduced pH conditions (pH 6.8) crabs were less likely to change from a suboptimal to an optimal shell than those in untreated sea water; those that did change shells took longer to do so. Crabs in the reduced pH treatment also showed significantly lower antennular flicking rates (the ‘sniffing’ response in decapods) and reduced movement. Thus, a reduction in sea water pH disrupts the resource assessment and decision-making processes of these crabs, indicating that the ability to acquire a vital resource may be influenced by both naturally occurring environmental cycles and anthropogenically induced environmental change.